Critical review of School Health & Nutrition Program for achieving Advance Preventive Healthcare for Children in Punjab - Bhatti, Muhammad Ajmal; Azhar, Muhammad Asad (Journal of Public Policy Practitioners, 2022)
The School Health and Nutrition (SHN) program was launched in year 2007-08 in different districts of Punjab, Pakistan. As the core of this program, School Health and Nutrition Supervisors (SHNS) were hired as the main agents to implement the program’s objectives. These SHNS were appointed at Basic Health Units (BHUs) and tasked with the objectives to screen the children in public schools, identify sick children, ensure their medical treatment, referrals, and follow-ups along with conducting health education sessions in their respective schools and communities. The current paper attempted to assess the performance of this program and suggested succinct measures to reform it in order to achieve its desired objectives. It included the analysis of the reasons and bottlenecks due to which the highlighted anticipated outcomes of this program could not be fully realized. After analyzing the qualitative and quantitative shortcomings in the design and implementation of this program, the current article recommends workable solutions based on strategic revisions in both the clinical as well as the procedural part of the program.